Cytomegalovirus myocarditis with rapid response to intravenous immunoglobulin therapy - Türe, Mehmet; Balık, Hasan; Bilici, Meki; Akın, Alper; Darakci, Savaş Mert; Yanmaz, Sercan Yücel (Journal of Surgery and Medicine, 2018)
Myocarditis is an inflammatory disease of the heart muscle. Most cases are caused by viral agents such as enteroviruses and adenoviruses. Cytomegalovirus is one of the more rare causes of viral myocarditis. In this article, case is reported of viral myocarditis diagnosed due to Cytomegalovirus infection and which then responded very rapidly to intravenous immunoglobulin treatment. This case report can be considered to contribute to literature as there are not enough data about intravenous immunoglobulin treatment results in Cytomegalovirus myocarditis.